Stochastic Modelling of Daily Rainfall for South West Monsoon Season of Bapatla, Andhra Pradesh - Kumar, K.N Raja; Kumar, Devendra (Journal of Agricultural Engineering, 2004)
The daily rainfall data for the year of 1988 to 2002 were used to develop stochastic models for Southwest monsoon season of Bapatla. The periodic component in the time series was determined by Fourier analysis and removed. The series were modelled by autoregressive (AR) and autoregressive moving average (ARMA) family of models. The goodness of fit of models were. tested by Box-Pierce Portmonteau test, Akaike Information Criterion, and criteria of good ness of fit tests. Based on goodness of fit tests, AR (2) and ARMA (2, 2) models were selected for daily rainfall of the Southwest monsoon season of Bapatla.